Analisis Kualitas Pendaftaran Merek di Direktorat Jenderal Hak kekayaan Intelektual - , Hefrandry Hutapea ([Yogyakarta] : Universitas Gadjah Mada, 2013)
As a member of WTO, Indonesia had to adjust all the rules in the regulation of Intellectual Property Rights TRIPs standards. Intellectual Property Rights (IPR) is the right to be able to enjoy economical of human intellectual abilities. DJHKI, the competent authority in managing IPR in Indonesia, responsible for providing services to the public to get any legal protection for intellectual property committed by the perpetrators of IPR particularly in terms of the brand. This study aims to analyze quality of service that has been done by DJHKI to the community, especially in the service mark registration of the perception of the service recipient. And for support, this research refers to research Brady and Cronin (2001) who tried to make up about the quality of service based on a previous study that covers three dimensions. The method is a descriptivestudy conducted in which the primary data collection through interviews using questionnaires to the respondents in this case the perpetrators IPR register her brand into DJHKI. Results of the questionnaire data was processed and analyzed using SPSS data processing program. From the analysis of the data with the model of Brady and Cronin (2001) it can be used to measure the quality trademark registration services in DJHKI through registrars brand perception on the performance of the service mark registration. Looks still a need to increase the performance of the service mark registration.